Price momentum profitability in the US tech stock market - Dyachenko, Veniamin (2019)
Trading momentum has been a highlighted theme during the last decades due to conflicting points of view within the academia and investment community. Despite the recurring studies regarding momentum, there are still no consensus about the significance of momentum returns neither about the causes behind it. In addition, the investor's community embraced the momentum effect which results in the creation of successive funds and Exchange-Traded-Funds (ETF) that follows momentum trading strategies. The aim of this paper is to observe the momentum effect in the United States Technological equity markets. This study looks at the 200 biggest tech firms in the United States, in the time-frame from 2008 to 2018, and finds empirical evidence of positive and significant momentum returns. Reasons for the observation of momentum returns might be explained by behavioural theories which theorize the effect of psychological biases in the investment decisions. The implication for this study aims to clarify the state of momentum trading strategies nowadays with tight focus on the tech industry.